Recreational Diving Practice for Stress Management: An Exploratory Trial - Beneton, Frédéric; Michoud, Guillaume; Coulange, Mathieu; Laine, Nicolas; Ramdani, Céline; Borgnetta, Marc; Breton, Patricia; Guieu, Regis; Rostain, J. C.; Trousselard, Marion (Frontiers in Psychology, 2017)
Background: within the components of Scuba diving there are similarities with meditation and mindfulness techniques. Perceived stress is known to be diminished during meditation practice. This study evaluates the benefits of scuba diving on perceived stress and mindful functioning. Method: A recreational diving group (n=37) was compared with a multisport control group (n=30) on perceived stress, mood, well-being and mindfulness by answering auto-questionnaires before and after a one-week long UCPA course. For the diving group, stability of the effects was evaluated one month later using similar auto-questionnaires. Results: An improvement in mood scale was observed in both groups. The divers showed a significant reduction on the perceived stress score with a sustainable effect. This was associated to an increase in mindfulness abilities. Conclusions: The practice of a recreational sport improves the mood of subjects reporting the thymic benefits of a physical activity performed during a vacation period. The health benefits of recreational diving appear to be greater than the practice of other sports in reducing stress and improving well-being.